HUMAN RESOURCES STRATEGY: AN EXPLORATORY STUDY AT PRIVATE SECONDARY SCHOOL IN JAGAT RAYA SCHOOL KEDONGDONG VILLAGE, CIREBON REGENCY-INDONESIA - Maula, Nurkholifatul (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2018)
The polemic of private schools has quite been a debate in Indonesia. There are many private schools with good quality in Indonesia that make their existence beat the public schools. However, it is inversely proportional to the private school in the village. Private schools in the village are quite alarming. This study aims to describe about human resources strategy in Jagat Raya school and the effect of human resources strategy on the school development. This study employed exploratory methods. In this case, the exploratory methods used to were interview methods, observation and document studies. This first objective was done by conducting interviews and direct observation. The second objective of this study was conducted by using document review. The result of this research, in terms of organization, on vision and mission planning, was conducted by discussing together with the teachers at school. The impact of the human resource strategy, in terms of the student quality during the last five years is quite increasing, and the national exam scores are quite improving from year to year. However, it is inversely proportional to the decreased number of students who enter each year. This condition is quite critical for the sustainability of the school.